2002
DOI: 10.1103/physrevb.65.094509
|View full text |Cite
|
Sign up to set email alerts
|

Order in driven vortex lattices in superconducting Nb films with nanostructured pinning potentials

Abstract: Driven vortex lattices have been studied in Nb films, in which natural random pinning coexists with artificial ordered arrays of defects ͑submicrometric Ni dots͒. Three different dynamic regimes are found: for low vortex velocities, there is a plastic flow regime in which random defects frustrate the effect of the ordered array; then, for vortex velocities in the range 1-100 m/s, there is a sudden increase in the interaction between the vortex lattice and the ordered dot array, associated to the onset of quasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…The details of the NbN film used for fabricating the triangular antidot array is shown in Table 1 line lattices [5][6][7]. Simulations on triangular antidot array by Reichhardt et al [17] corroborate this scenario.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The details of the NbN film used for fabricating the triangular antidot array is shown in Table 1 line lattices [5][6][7]. Simulations on triangular antidot array by Reichhardt et al [17] corroborate this scenario.…”
Section: Resultssupporting
confidence: 64%
“…Horng et al [4] demonstrated the absence of certain matching periods in the case when interstitial vortices nucleate in the antidot array samples. Furthermore, there exists experimental evidence for a possible reordering of the nucleated interstitial vortices leading to a "super matching (SL)" flux line lattices [5][6][7]. Within the theoretical scenario proposed by Mkrtchyan and Shmidt [8], the maximum number of vortices captured by an isolated antidot (columnar defect) of diameter D is given by the saturation number (n s ) where, [9].…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed experimental exploration of many phenomena regarding static and dynamic properties of the VL. The most remarkable effects arising in this kind of nanostructured superconductors include commensurability between the VL and the periodic array of pinning centers, [2][3][4][5][6][7][8][9][10][11][12] competition between random and periodic pinning, 13 channeling effects in the VL dynamics, 14 or the ratchet effect. 15 Interestingly, much of the physics related to VL dynamics on periodic pinning potentials might apply to other systems in which transport of small particles takes place through fixed periodic potentials, as for instance colloids, 16 electrons in periodic antidot arrays, 17 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Below a threshold current value the vortex lattice velocity is too low and the intrinsic and random potentials overcome the periodic pinning, therefore the periodic pinning effect vanishes; above a second threshold current value ͑high driving force͒ the vortex lattice velocity is enhanced and the vortex lattice does not undergo the periodic potentials. 13 The competition between the vortex-vortex interaction and the asymmetric potentials could be explored by increasing the applied magnetic field, which means more vortices per array unit cell. Figure 3 shows ratchet and transverse effects when the number of vortices increase to 4 ͓Fig.…”
mentioning
confidence: 99%
“…The suitable temperatures and driving forces for exploring ratchet and matching effects have been discussed elsewhere. 6,13 In summary, the temperature should be very close to the superconducting critical temperature and the driving forces ͑currents͒ should be between the two current values. Below a threshold current value the vortex lattice velocity is too low and the intrinsic and random potentials overcome the periodic pinning, therefore the periodic pinning effect vanishes; above a second threshold current value ͑high driving force͒ the vortex lattice velocity is enhanced and the vortex lattice does not undergo the periodic potentials.…”
mentioning
confidence: 99%